(untitled) (Global Journal of Management and Business Research, 2017)
The presence of a Six Sigma system when integrating strategic factors into a Six Sigma activity improves the probability of successful implementation. However, few systematic studies have investigated the relationship between business strategy and Six Sigma. This paper presents a framework for linking Six Sigma with business strategy for the purpose of obtaining competitive advantage. To examine the conditions that are conducive to Six Sigma long-term success, we conducted workshop consensus activities and carried out Six Sigma strategy development. Using these workshop consensus activities, we integrated business strategy development into a Six Sigma implementation framework that allocates organizational resources to meet core customer requirements.